The pollen record from marine core MD03-2607 from offshore Kangaroo Island spanning the last 125 ka; implications for vegetation changes across the Murray-Darling Basin. Issue 7 (3rd October 2021) - De Deckker, P.; van der Kaars, S.; Haberle, S.; Hua, Q.; Stuut, J.-B. W.
Abstract: A palynological record spanning the last glacial–interglacial period was derived from high-resolution, deep-sea core MD03-2607, located near Kangaroo Island in South Australia. The core site lies opposite the mouth of the River Murray that, together with the Darling River, drains the extensive (∼1.6 × 10 6  km 2 ) Murray-Darling Basin (MDB). The record comprises 120 samples and is compared with detailed records of sea-surface temperature (SST), the C3 /C4 plant ratio obtained from the δ 13 C of n -alkanes from leaf waxes, the fluvial clay fraction and its neodymium isotopic composition, airborne dust and the biomass-burning component levuglosan. The chronology of the core is robust; it is built on 24 radiocarbon dates derived from planktic foraminifera, 16 optically stimulated luminescence dates, plus 12 tie points linked to the astronomically tuned marine isotopic record. Algal remains are found in nearly all samples supporting our postulation that the palynoflora is predominantly waterborne. Major findings are that the gymnosperm Callitris, together with high percentages of herb pollen (mostly C3 plants), is predominant during cold, arid phases, whereas Eucalyptus, is predominant during warmer and wetter periods. High charcoal concentration coincides with high percentages of Eucalyptus, mostly during wet and warm periods. Using the geochemistry of the core's fluvial sediments, it has been possible to identify when water-transported palynoflora and charcoal originated from the Murray sub-basin (consisting of the River Murray and its main tributaries but not from central or western South Australia). During those periods, rainfall principally originated from the southeastern Indian Ocean. When the Darling sub-basin was the main source of the palynoflora, rainfall must have instead originated from northern Australia. The eolian dust record from the core shows that the dust signal generally coincides with the increased values in herb pollen, in particular during the Last Glacial Maximum (LGM) when, in addition to high herb percentages, Callitris representation also increased. This dry landscape taxon likely colonised the then-exposed Lacepede Shelf during this period of extreme low sea-level. There is a good correspondence between SST and mean annual precipitation reconstructed from the pollen counts. During warm phases in the ocean, Eucalyptus was the dominant tree taxon, especially for the entirety of Marine Isotope Stages (MIS) 5, plus MIS 3 and MIS 1. Charcoal levels were particularly low during the dry phases MIS 4 and 2, and even more so during the LGM. KEY POINTS: We provide a very detailed pollen diagram from a deep-sea core taken offshore from the mouth of the River Murray. This record details vegetation changes in the Murray-Darling Basin spanning the last glacial/interglacial cycle. The pollen record is compared with other proxies obtained from the marine core, such as sea-surface temperature, changes in C3 /C4 plants percentages, geochemical analyses of terrigenous sediments that inform on the origin of the sediments reaching the ocean and by implication the origin of the pollen. Charcoal counts obtained from the core are compared with the pollen spectra and clearly indicate the large incidence of fires during wet and warm periods when Eucalyptus pollen was abundant. Low charcoal counts occur during dry and cold phases when Callitris pollen were predominant over Eucalyptus.